Incomplete Explanation in Determining Oxidation Number: A Case Study on Chemistry Program Students - Basuki, R.; Amanda, H.; Bemis, R.; Lisma, A.; Yusnaidar, Y. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
The term Ã¢â‚¬Å“oxidation numberÃ¢â‚¬Â and related concept such as Ã¢â‚¬Å“electronegativityÃ¢â‚¬Â and Ã¢â‚¬Å“formal chargeÃ¢â‚¬Â appear frequently in both elementary and advance chemistry text. However, it is evident from the literature (or textbooks) that these terms are often viewed to be synonymous. Incomplete explanation of the fundamental concept of oxidation number can lead that conclusions pertaining to such a misleading interpretation. This research was conducted to review the concepts from common used high school chemistry textbooks and these concepts were then transformed to 6 number open minded problems. These problems were then tested to 40 first semester chemistry program students in the University of Jambi who joining Basic Chemistry course. The result was about 80% of students give the right answer in determining oxidation number (problem number 1). But, in the certain molecule (problem number 2) they canÃ¢â‚¬â„¢t determine correctly because they couldnÃ¢â‚¬â„¢t use the Ã¢â‚¬Å“RuleÃ¢â‚¬Â from initial understanding in high school. For the next problem (4a), none of the students give the right oxidation number of an atom and all of them canÃ¢â‚¬â„¢t explain precisely correlation among oxidation number, electronegativity, and formal charge. The intent of this paper is to clarify the notion of oxidation number, electronegativity, and formal charge, describe their relationship (especially for high school chemistry textbooks), and criticize upon misleading application.